Physical Activity Patterns in Rural-Residing Spousal Caregivers and Cardiac Surgery Patients in the First 6 Months Post-Surgery - Paula Schulz; Lani Zimmerman; Patrik Johansson; Melody Hertzog; Sue Barnason (Rural Nurse Organization; Binghamton University, 2014)
Background: Caregivers (CGs) play a major role in cardiac surgery patients' adoption of secondary prevention strategies.  Little research has examined spousal CGs activities to preserve their own health and support patients' heart-healthy behaviors. Purpose: The aims of this descriptive pilot study are to: 1) compare cardiovascular (CV) risk factors and physical activity (PA) levels and 2) examine trajectories of change in PA patterns at 3 and 6 weeks and 3 and 6 months after cardiac surgery. Sample:  28 rural residing adult (> 60 years) cardiac surgery patients and their spousal CGs. Methods: PA data was obtained from ActiGraph® accelerometers mailed to dyads at 4 time points after cardiac surgery. Descriptive analyses and multivariate hierarchical modeling were used to describe and identify PA patterns. Findings: The dyads were older (CG M = 68.5 ± 6.6, Patient M = 70.7 ± 6 years) with primarily female CGs (92%) residing in small rural towns (n=26, 46.4%) or farm/ranch (n=16, 28.6%). CV risk factor concordance was evident particularly for hypertension (60.7%) and hypercholesterolemia (25%). CGs and patients spent the majority of time in sedentary activity. Most patients (89.3%) completed cardiac rehabilitation programs and increased their mean minutes/day spent in moderate to vigorous PA over the 4 time points (13.3 ± 15.6 to 22.6 ± 24.4). However, CGs mean minutes/day remained virtually unchanged over time (15.8 ± 20.8 to 12.7 ± 11.7). Considered as dyads, 38% (n=8) showed essentially no change for either member, but for 29% (n=6) the caregiver showed no change while the patient activity increased. Conclusions: CGs were similar in age and comorbidities to their spouses, however, CGs were less likely to increase their PA levels. Health disparities in CVD mortality in the rural population may have additional impact and underscores the need for future targeted interventions addressing CV risk in CGs. Keywords:  health behavior, cardiac surgery, caregiver, risk factors DOI:  http://dx.doi.org/10.14574/ojrnhc.v14i2.330